The antibacterial activity and mechanism of a novel peptide MR-22 against multidrug-resistant Escherichia coli - Tian, Chunren; Zhao, Na; Yang, Longbing; Lin, Fei; Cai, Ruxia; Zhang, Yong; Peng, Jian; Guo, Guo (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Bacterial infections have become serious threats to human health, and the excessive use of antibiotics has led to the emergence of multidrug-resistant (MDR) bacteria. E. coli is a human bacterial pathogen, which can cause severe infectious. Antimicrobial peptides are considered the most promising alternative to traditional antibiotics. Materials and methods The minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and hemolytic activity were determined by the microdilution method. The antimicrobial kinetics of MR-22 against E. coli were studied by growth curves and time-killing curves. The cytotoxicity of MR-22 was detected by the CCK-8 assay. The antimicrobial activity of MR-22 in salt, serum, heat and trypsin was determined by the microdilution method. The antimicrobial mechanism of MR-22 against drug-resistant E. coli was studied by Scanning Electron Microscope, laser confocal microscopy, and Flow Cytometry. The in vivo antibacterial activity of MR-22 was evaluated by the mice model of peritonitis. Results and discussion In this study, MR-22 is a new antimicrobial peptide with good activity that has demonstrated against MDR E. coli. The antimicrobial activity of MR-22 exhibited stability under conditions of high temperature, 10% FBS, and Ca2+. However, a decline of the activity was observed in the presence of Na+, serum, and trypsin. MR-22 had no significant cytotoxicity or hemolysis in vitro. SEM and fluorescent images revealed that MR-22 could disrupt the integrity of cell membrane. DCFH-DA indicated that MR-22 increased the content of reactive oxygen species, while it decreased the content of intracellular ATP. In mice model of peritonitis, MR-22 exhibited potent antibacterial activity in vivo. These results indicated that MR-22 is a potential drug candidate against drug-resistant E. coli.